QuartimaxFactor Analysis and Centroid Hierarchical Cluster On Visit Lombok Sumbawa Program (VLS) - Komalasari, Desy (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
West Nusa Tenggara Province seeks to promote tourism in its region through a program called Visit Lombok Sumbawa ( VLS ) 2012. This is done because tourism can make a major contribution to the regional economy of NTB. The method used to determinethe effect factors ofthe tourist traffic is factor analysis using the quartimax rotation,and for the grouping of tourists using centroid hierarchichalcluster techniques. Fromthis research were obtained four main factors that affect tourist arrivals in this program, including internal factors derived from tourism, personal factors, hygiene factors and promotion factors. In cluster analysis that using centroid hierarchichal clusterhas formed 3 type tourist clusters,where cluster 1 the group of tourists who tend the internal factors and personal factors, cluster 2 the group of tourists who tend to promotion factor, and cluster 3 the group of tourists who tend thehygiene factor in visiting the sights